Generation of an iPSC cell line (VANYHHi001-A) from a patient with cardiac arrythmias carrying CACNA1D, SCN5A, and DSP variants - Yvonne Sleiman; Jean-Baptiste Reisqs; Reina Bianca Tan; Frank Cecchin; Mohamed Chahine; Mohamed Boutjdir (Stem Cell Research)
Progressive cardiac conduction defect often associated with variants in sodium voltage-gated channel SCN5A gene and variants in the L-type calcium voltage-gated channel CACNA1D gene are implicated in sinoatrial node dysfunction. We generated an induced pluripotent stem cell line (iPSC) from a 13-year-old patient with history of conduction system disease and ventricular tachycardia, carrying variants in SCN5A (c.2618C > G), CACNA1D (c.3786G > T), and DSP (c.1582C > G). The generated iPSC line exhibited pluripotency markers, differentiated into the three embryonic germ layers, and maintained a normal karyotype. This iPSC line offers insights into the pathophysiological mechanisms of cardiac arrhythmias and personalized therapies development.